Canada-United States-Mexico Trilateral Cooperation on Childhood Obesity Initiative - Cristina Rabadán-Diehl; Margarita Safdie; Rachel Rodin
ABSTRACT Childhood obesity is an important public health problem that affects countries in the Americas. In 2014, Pan American Health Organization (PAHO) Member States agreed on a Plan of Action for the Prevention of Obesity in Children and Adolescents in an effort to address the impact of this disorder in the Americas region. The interventions laid out in this regional plan are multi-faceted and require multi-sectoral partnerships. Building on a strong history of successful trilateral collaboration, Canada, Mexico, and the United States formed a partnership to address the growing epidemic of childhood obesity in the North American region. This collaborative effort, known as the Trilateral Cooperation on Childhood Obesity Initiative, is the first initiative in the region to address chronic noncommunicable diseases by bringing together technical and policy experts, with strong leadership and support from the secretaries and ministers of health. The Initiative's goals include increasing levels of physical activity and reducing sedentary behavior through 1) increased social mobilization and citizen engagement, 2) community- based outreach, and 3) changes to the built (man-made) environment. This article describes the background and development process of the Initiative; specific goals, activities, and actions achieved to date; and opportunities and next steps. This information may be useful for those forming other partnerships designed to address childhood obesity or other complex public health challenges in the region.